The importance of the Veterinarian in Public Health (Research, Society and Development, 2021)
It was from Resolution No. 287 of October 8, 1998 of the National Health Council - CNS that veterinarians started to be considered health professionals, and, since then, it is possible to notice the expansion of the field of action of these professionals and the its importance with regard to public health, given that 60% of human diseases are zoonotic and 75% of these diseases originate in wild fauna, and the only professionals qualified to prevent, diagnose and treat these rich in animals and prevent reach humans is the veterinary medicine professional. The aim of the study was to describe the increasingly holistic training of veterinarians, their performance in different areas of Brazilian public health and their importance for unique health – the interface between animal, human and environmental health. A literature review was used through data collection in journals, websites, articles and journals. The research resulted in a wealth of very varied information about some fields of activity of veterinarians in public health, and raised important debates about what still leads some health managers to resist hiring this professional, considering that in the year of 2018, among the 5,570 Brazilian municipalities, only 48 of these had the veterinarian in the teams of the Expanded Family Health Center - NASF, calling into question their relevant role in the preservation and promotion of human health, and not just animal health.